(untitled) (Research, Society and Development, 2022)
All over the world, many agro-industrial residues are produced daily from different types of industrial processes. Emphasizing those carried out by pulp and juice industries that discard most of the total weight of fruits (peels and seeds). These residues contain large amounts of nutrients, such as sugars, minerals and proteins, which can be biotransformed into molecules of technological interest through the application of biotechnological processes. Among them, the fermentative processes with filamentous fungi come as a promising alternative, as these microorganisms are reported as major producers of secondary metabolites with medical and pharmaceutical application. Such as, for example, biocolorants, which are substances that provide color and can add biological activity to products, such as antioxidant and antimicrobial action. The present work is a narrative review on the potential use of different types of agro-industrial residues as nutritive substrates for fungal growth and the industrial production of their bioactive metabolites.